Identità e diritti delle donne. Per una cittadinanza di genere nella formazione - Pace, Roberta (Premio Tesi di Dottorato, 2010)
The gender gap that traverses the planet is one of the most blatant democratic failures, and it is no longer an additional or accessory issue but one that is crucial to the wellbeing of both men and women. The strategies of intervention mapped out in international programmes (gender mainstreaming and empowerment) underscore the commitment and the responsibilities of educational processes. The aim of the book is to stimulate reflection on the role of education in the establishment of gender identities and in fostering the human rights of women in contemporary society. With a view to an interdisciplinary feminist and feminine analysis, which is essential to the development and interweaving of gender issues and points of educational interest, the question is posed as to whether a new sensitivity and a more widespread gender culture could successfully trigger daily practices of gender-oriented education.